Do Missing Link Community Smell Affect Developers Productivity: An Empirical Study - Ahammed, Toukir; Ahmed, Sumon; Khan, Mohammed Shafiul Alam (Knowledge Engineering and Data Science, 2021)
Missing link smell occurs when developers contribute to the same source code without communicating with each other. Existing studies have analyzed the relationship of missing link smells with code smell and developer contribution. However, the productivity of developers involved in missing link smell has not been explored yet. This study investigates how productivity differs between smelly and non-smelly developers. For this purpose, the productivity of smelly and non-smelly developers of seven open-source projects are analyzed. The result shows that the developers not involved in missing link smell have more productivity than the developers involved in smells. The observed difference is also found statistically significant.